2021
DOI: 10.1016/j.trip.2021.100461
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the changes in travel behavior in a developing country amidst the COVID-19 pandemic: Insights from Metro Cebu, Philippines

Abstract: This article investigates changes in travel behavior from selected urban cities in Metro Cebu, Philippines during the COVID-19 pandemic a year after the first lockdown. Different categories of community quarantine and granular lockdowns have since been imposed to curb the spread of the virus. An online survey was distributed to analyze socio-demographic characteristics and reasons for traveling in relation to weekly trip frequency before and during pandemic. These are presented and analyzed through data visual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 36 publications
1
16
0
Order By: Relevance
“…Aside from the public transportation system, past researchers also evaluated the behavior of passengers during the COVID-19. Mayo et al (2021) evaluated the travel behavior of Cebuanos around the cities of Metro Cebu, Philippines. They found that individuals frequently traveled to work pre-pandemic but shifted to buying necessities a year after the onset of the pandemic.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Aside from the public transportation system, past researchers also evaluated the behavior of passengers during the COVID-19. Mayo et al (2021) evaluated the travel behavior of Cebuanos around the cities of Metro Cebu, Philippines. They found that individuals frequently traveled to work pre-pandemic but shifted to buying necessities a year after the onset of the pandemic.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Public transport services were not permitted to operate at the onset of coronavirus disease (COVID-19) in the Philippines. Most importantly, the governing bodies had only permitted private cars and specific company automobiles to use the road ( Mayo, Maglasang, Moridpour, & Taboada, 2021 ; Vallejo & Ong, 2020 ). Additionally, people could not leave their homes except for healthcare workers and other essential workers ( Gregorio, 2020 ; Parrocha & Dela Cruz, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is the measure implemented, for example, in the Philippines, Indonesia and Colombia (e.g. Mayo et al, 2021 , Khoirunurrofik et al, 2021 , Guzman et al, 2021 ). Besides lockdowns, other non-pharmaceutical interventions – which may be less drastic – include containment strategies such as the declaration of general holidays; closure of educational institutions, markets and malls; and restriction on religious gatherings, as was done in Bangladesh (Zafri et al, 2021).…”
Section: Review Of Literature On Service Contractingmentioning
confidence: 99%
“… Kim, 2021 ). Focusing on papers from the Global South, these studies include: establishing the risk factors contributing to Covid (Rahman et al, 2021; Kartal et al, 2021 ); examining the changes due to the pandemic on travel behavior, mode use, mobility patterns in Bangladesh ( Anwari et al, 2021 ; Zannat et al, 2021), India ( Bhaduri et al, 2020 , Pawar et al, 2020 ; Zannat et al, 2021), Nigeria ( Mogaji, 2020 , Ajide et al, 2020 ), Dominican Republic ( La Paix, 2021 ), Philippines ( Mayo et al, 2021 ) and China ( Yang et al, 2021 ); and finally, assessing the effectiveness of policies and interventions on mobility restrictions or virus transmission (e.g. Khoirunurrofik et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%